Health care provider recommendations for reducing cancer risks among women with a BRCA1 or BRCA2 mutation. (26th August 2013) - Metcalfe, KA; Kim‐Sing, C; Ghadirian, P; Sun, P; Narod, SA
<x xml:space="preserve">Abstract</x> There is a significant variation in the uptake of cancer risk reducing options by women with a BRCA1 or BRCA2 mutation. It is currently unclear why these differences exist and it is possible that recommendations vary between providers and these influence patient decisions. Eligible health care providers who provide genetic counseling for hereditary breast and ovarian cancer families in Canada were identified. Each provider was asked to complete a study specific questionnaire that included their opinion of various cancer risk reduction options and their recommendations for specific cases. Respondents recommended prophylactic oophorectomy more often than prophylactic mastectomy or tamoxifen for women with a BRCA1 or BRCA2 mutation (p < 0.0001). Fewer than half of the respondents agreed with the recommendation for prophylactic mastectomy, and a minority of the respondents supported the recommendation for tamoxifen for chemoprevention. The majority of Canadian genetics health care providers adhere to the National Comprehensive Cancer Network (NCCN) Guideline of recommending prophylactic oophorectomy to mutation carriers, however, the minority of genetics health care providers recommend either prophylactic mastectomy or tamoxifen.